PENERAPAN METODE UTAUT UNTUK MEMPREDIKSI BEHAVIORAL INTENTIONS USER DALAM MENGGUNAKAN APLIKASI ZABBIX - Beni Mediyanto; Irfan Mahendra (LPPM Nusa Mandiri, 2017)
Use of information technology is essential for the company, because it can increase the effectiveness and efficiency of the company's performance. But the application of information technology is not always successful. One of the critical success factors of the application of information technology is the attitude of the users who use the technology. UTAUT also used by some researchers to look at the intentions and behavior of users of information technology in several areas of the company. Therefore, this study was developed by adopting the model to see the intentions of the user UTAUT Zabbix Application in PT Media Nusantara Citra Tbk. Four constructs of UTAUT used as determinants that influence the behavioral intentions (behavioral intentions user), namely performance expectancy, effort expectancy, social influence and facilitating conditions. Data in the study were tested by means of SEM (Structural Equation Model). SEM is a statistical analysis tool used to complete multilevel research model simultaneously. SEM can be used to solve equations with variables that make up a path. Data obtained through 50 questionnaires distributed to PT Media Nusantara Citra Tbk and in particular the IT Infrastructure Division. The analysis showed that behavioral intentions are significantly influenced by the user, effort expectancy and facilitating conditions, while the performance expectancy and social factors influence found no significant effect.